Utilitarianism : Restorations ; Repairs ; Renovations. - Braybrooke, David (Toronto studies in philosophy., 2014)
Substituting comparative censuses for the hedonistic calculus that figures in standard utilitarianism, Braybrooke excludes gratuitous sacrifices also of happiness short of life-sacrifices.